Efektivitas Board Of Peace Dalam Perspektif Hukum Perjanjian Internasioanal Terhadap Penyelesaian Konflik Antar Negara - Varik Farsyak; Laura Shafa Qurratun Nisa; Syafariah Nata Putri (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
Interstate conflict is a constantly evolving phenomenon within the dynamics of international relations and demands an effective dispute resolution mechanism based on international law. This study aims to analyze the legal standing and basis of the Board of Peace from the perspective of international treaty law and to examine its effectiveness and implications for non-member states. The research method used is normative legal research with a statutory and conceptual approach, using primary, secondary, and tertiary legal materials analyzed qualitatively. The results show that the Board of Peace cannot be categorized as a legitimate international organization if it is not established through an international treaty as a constitutive instrument, thus lacking international legal personality or legally binding force. Consequently, its decisions are non-binding and rely more on a persuasive approach. Furthermore, the Board of Peace's effectiveness towards non-member states is limited and indirect, but still has implications in political, legal, economic, and security aspects, such as the formation of international norms and its influence on regional stability. Thus, the success of the Board of Peace is highly dependent on legal legitimacy, state participation, and the dynamics of international relations.